Peran Kader Kesehatan dalam Tindakan Penemuan Kasus Tuberkulosis dengan Pendekatan Theory Planned of Behaviour di Wilayah Kerja Puskesmas Bendosari - Novi Indah Aderita; Chusnul Chotimah - Poltekkes Bhakti Mulia (Unit Penelitian dan Pengabdian Masyarakat Politeknik Kesehatan Bhakti Mulial, 2018)
Abstract: Tuberculosis (TB) in the world continues to increase, in 2012 as many as 8.6 million people, in 2013 as many as 9 million people and in 2015 as many as 9.6 million people. It is estimated that in Indonesia every year there are 450,000 new cases, and a third are not yet covered by health services. TB case finding is the first step in TB prevention activities. Efforts to find TB cases need to involve many health sectors such as health cadres. The role of health cadres is related to behavioral interventions with the Theory of Planned Behavior (TPB) approach. This study aims for the role of health cadres in the action of finding tuberculosis cases with the planned of behavior theory approach in the work area of the bendosari health center. The design of this study using observational analytic. The study was conducted in May-June 2017 in the Bendosari Community Health Center work area. The research subjects were 60 health cadres who were chosen by fixed disease sampling technique. Endogenous variables consist of: intention and discovery of TB cases. Exogenous variables consist of: attitudes, norms and behavioral control. Instruments used in data retrieval are questionnaires and analyzed by path analysis. The results of this study were: intention (b = 4.96; 95% CI = 2.78 to 7.14; p = 0.001) related to TB case finding. Attitudes (b = 1.87; 95% CI = 0.08 to 3.66; p = 0.040), subjective norms (b = 1.47; 95% CI = 0.35 to 3.29; p = 0.113), perception of behavioral control (b = 2.31; 95% CI = 0.92 to 2.69; p = 0.001), related to intention. The results show that the increased intention to directly improve the discovery of tuberculosis. Increased attitudes, norms and behavioral control directly increase the intention in the discovery of TB. Collaboration between health cadres and health workers is needed for TB case finding in the community.Keyword: Health Caders, Actions of Tuberculosis Cases, Theory of Planned BehaviourAbstrak: Penyakit tuberkulosis (TB) di dunia terus mengalami peningkatan, tahun 2012 sebanyak 8,6 juta jiwa, tahun 2013 sebanyak 9 juta jiwa dan tahun 2015 sebanyak 9,6 juta jiwa. Diperkirakan di Indonesia setiap tahun terdapat 450.000 kasus baru, dan sepertiganya belum terjangkau pelayanan kesehatan. Penemuan kasus TB merupakan langkah pertama kegiatan penanggulangan TB. Upaya penemuan kasus TB perlu melibatkan banyak sektor kesehatan seperti kader kesehatan. Peran kader kesehatan berkaitan dengan intervensi perilaku dengan pendekatan Theory of Planned Behavior (TPB). Penelitian ini bertujuan untuk menganalisis peran kader kesehatan dalam tindakan penemuan kasus tuberkulosis dengan pendekatan theory planned of behavior di wilayah kerja Puskesmas Bendosari. Desain penelitian ini dengan menggunakan analitik observasional. Penelitian dilaksanakan pada Mei–Juni 2017 in wilayah kerja Puskesmas Bendosari. Subjek penelitian berjumlah 60 kader kesehatan yang dipilih dengan teknik fixed disease sampling. Variabel endogen terdiri dari: niat dan penemuan kasus TB. Variabel eksogen terdiri dari: sikap, norma dan kendali perilaku.instrumen yang digunakan dalam pengambilan data adalah dengan kuesioner dan dianalisis dengan path analisis. Hasil menunjukkan bahwa peningkatan niat meningkatkan secara langsung penemuan tuberkulosis. Peningkatan sikap, norma dan kendali perilaku meningkatkan secara langsung niat dalam penemuan TB. Kerjasama antara kader kesehatan dengan tenaga kesehatan diperlukan untuk penemuan kasus TB di masyarakat.Kata Kunci: Kader kesehatan, Penemuan Kasus TB, Theory Planned Behaviour